Pengembangan Teknologi Metaverse Ekosistem E-Mobility Pada Pameran Teknologi International Berbasis Augmented Reality - Noorlela Marcheta; Dewi Yanti Liliana; Agus Setiawan; Ilham Sidiq; Asep Kurniawan (Sekawan Institut, 2024)
Augmented Reality (AR) can be used as a new technology in organizing virtual and paperless exhibitions to make the products on display more attractive and updated regularly. This can happen because AR is a technology that integrates the virtual and real worlds. AR has been widely used as a medium to assist in providing information in real-time in an interesting, interactive, and educational way. This journal explains the development of AR media and its feasibility as an international promotional media in introducing the E-Mobility Ecosystem. The E-Mobility Ecosystem is a PENTA-branded convertible electric car, one of PNJ's superior technologies. The Hannover Messe'23 exhibition with the theme